1966
DOI: 10.1149/1.2424170
|View full text |Cite
|
Sign up to set email alerts
|

The Electrode Potential of Evaporated Aluminum Films in Chloride Solution

Abstract: not Available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

1981
1981
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…The OCP drop at the beginning of the test could be linked to the dissolution of the protective oxide [27]. Importantly, Hagyard et al showed that the potential rose to a peak at the beginning of the immersion and that this increase was attributed to the dissolution of aluminum and to the formation of the protective oxide [28,29]. This reaction was very quick and, thus, is rarely observed, which was the case in this study because no peak was visible in Fig.…”
Section: Corrosion Susceptibility Of the 2050 Alloy During Continuous Immersion Testsmentioning
confidence: 49%
“…The OCP drop at the beginning of the test could be linked to the dissolution of the protective oxide [27]. Importantly, Hagyard et al showed that the potential rose to a peak at the beginning of the immersion and that this increase was attributed to the dissolution of aluminum and to the formation of the protective oxide [28,29]. This reaction was very quick and, thus, is rarely observed, which was the case in this study because no peak was visible in Fig.…”
Section: Corrosion Susceptibility Of the 2050 Alloy During Continuous Immersion Testsmentioning
confidence: 49%
“…The initial step must be the adsorption of water onto the fresh metal surface which proceeds rapidly to completion immediately behind the stylus Fe + H20 ~ Fe.H2Oads [1] Reaction [1] is followed by one of two mechanisms as follows Fe'H2Oads ~ FeOHa~s + H + + e- [2] or Fe'H2Oads .~ Fe 'OH-ads + H + [3] Fe'OH-ads-~ FeOHads ~ e- [4] By considering the coverage of adsorbed water to be complete, and the coverage of FeOH to be small, reaction [2] gives…”
Section: Discussionmentioning
confidence: 99%
“…and OE/O log is ----118 mV, OE/O pH ----0 for ~ -----0.5. Reaction [3] forms a rapid equilibrium prior to reaction [4], with Ks = 0[H+]/(1 --0) [6] where 0 is the coverage of adsorbed OH-, and…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations